Producing cement clinker assemblages in the system: CaO-SiO2-Al2O3-SO3-CaCl2-MgO. (June 2021) - Simoni, Marco; Hanein, Theodore; Duvallet, Tristana Y.; Jewell, Robert B.; Provis, John L.; Kinoshita, Hajime
Abstract: The cement industry is carbon-intensive, and the valorisation of industrial side-streams/residuals for use as alternative raw materials can enable the cement industry to reduce its carbon footprint as well as promote resource efficiency. Apart from key clinker ingredients such as CaO, Al2 O3, and SiO2, industrial residues can also contain MgO, CaCl2, and SO3 . Therefore, this study investigates the formation of cement clinker assemblages in the system CaO-SiO2 -Al2 O3 -SO3 -CaCl2 -MgO at temperatures ranging between 1100 and 1300 °C. The production of a clinker composed mainly of alinite and ye'elimite is first attempted; it is found that these phases cannot be simultaneously produced. Ternesite is also not compatible with alinite under the conditions studied. Wadalite is compatible with both ye'elimite and ternesite, while ternesite is also compatible with chlormayenite at 1150 °C. Additionally, the low-temperature formation of alite was also observed with the presence of CaCl2 in the raw-material mix. Highlights: Alinite formation conditions are optimised. Ye'elimite and alinite cannot be simultaneously produced. Ternesite and chlormayenite are compatible at 1150 °C. Alite is formed at a reduced temperature of 1300 °C. Wadalite and chlorellestadite can incorporate chloride in cement clinker assemblages.